LEGAL PROTECTION OF INDIGENOUS LAW COMMUNITIES OVER CUSTOMARY FORESTS IN KERINCI REGENCY - Pranata, Taufik Halim; Sarwani , Raden (Communale Journal, 2024)
The rights of the Indigenous Communities to natural resources, land, and forests have not been explicitly regulated in a single legislative act, yet the control of the Indigenous Law Communities  (abbreviated as ILC) over customary forests is established. The customary forests in Kerinci Regency have been officially designated as customary forests based on the Minister of Environment and Forestry Decree, which the local ILC manages based on the Decree of the Regent of Kerinci. The control of customary forests requires recognizing and confirming the ILC through Regional Regulations  based on Law No. 41 of 1999 on Forestry. The sustainability of the ILC, as the rightful holders of customary forest rights, can be threatened if not recognized by the Regional Government. The research method employed is empirical juridical. The research findings indicate that the customary forests in Kerinci Regency have been designated as customary forest areas or proprietary forests as stipulated in the Minister of Environment and Forestry's Decree, with the recognition of each ILC right holder's existence based on the Decree of the Regent of Kerinci. Although the Regent's Decree does not adequately explain the status, structure, and customary institutions managing the customary forests, it implicitly acknowledges the existence of the ILC entitled to them. As a region with the most significant number of customary forests in Jambi Province, it is expected that the Kerinci Regency Government can draft regulations concerning the ILC.